Larangan Penggunaan Smartphone di Sekolah terhadap Prestasi Belajar Siswa - Siti Khadijah; R. Intan Invana Apriani (KOLONI, 2026)
Uncontrolled smartphone use can cause digital distraction, which affects students' concentration and academic achievement. To address this issue, SMPN 42 Bekasi implemented a policy prohibiting smartphone use at school in order to create a more orderly and conducive learning environment. This study aims to determine the effect of the smartphone-use prohibition policy on the learning achievement of students at SMPN 42 Bekasi. The study employed a quantitative approach using a survey method. The population consisted of 512 students, with a sample of 84 students selected through stratified random sampling. The independent variable was the prohibition of smartphone use, measured through the indicators of rule scope, trust, compliance, and supervision. The dependent variable was learning achievement, which included cognitive, affective, and psychomotor aspects. Data were collected using a Likert-scale questionnaire and analyzed through validity testing, reliability testing, simple linear regression, t-test, and coefficient of determination analysis. The results showed that the prohibition of smartphone use had a positive and significant effect on students' learning achievement. This was evidenced by a t-value of 8.572, which was greater than the t-table value of 1.989, with a significance value of 0.000 < 0.05. In addition, the coefficient of determination (R Square) was 0.473, indicating that the prohibition of smartphone use contributed 47.3% to students' learning achievement, while the remaining 52.7% was influenced by other factors outside the scope of this study. Therefore, the policy of prohibiting smartphone use contributes to improving students' learning achievement.